Saberes, correção e normalização no contexto da educação especial - Scheid, Matilde (Universidade do Vale do Rio do Sinos, 2007)
In this dissertation, my proposal is to analyse the interdisciplinar and multiprofessional staff who acted in the Especial Education context of a Municipal School District situated in “Vale do Rio dos Sinos” from the period of 1983 to 2003, as well as problematize the discourses that operate on these staffs which are composed by specialists from the Education and Health area. This study takes a post-structuralist perspective which approaches the studies of Michel Foucault. The corpus of this research was selected by twenty annual reports made by these staffs and was discussed in a archgenealogical approach. The analytical tools that were used – discourse, correction and normalization – allowed this study to get articulated by considering two analytical fronts: specialized knowledge and correction. This organization permitted the analysis of the knowledge that operate on these stuffs as well as their articulation to establish the subjects submitted to special education in different school places. I understand
Keywords: equipe; formação; interdisciplinaridade; política educacional; prática pedagógica; educação especial; correction; interdisciplinarity; normalization; special education; discourse; Ciências Humanas